Wisata Puri: Strategi Memasarkan Bali sebagai Educational Tourism Destination - Sudiarta, I Nyoman Sudiarta; Oka Karini, Ni Made; Juwita Sari, W. Citra (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2022)
The purpose of this study is to analyze the tourism of the castle from the marketing aspect (potential / product and tourist/market aspects) to build a new concept of Bali as an Educational Tourism Destination. This research was started by conducting a literature study to find out the tourism potential of the castle from various journals, proceedings, and reference books by searching on the google search engine related to